Rhetoric and the Dead Sea Scrolls Purity, Covenant, and Strategy at Qumran - McComiskey, Bruce, 1963- (Penn State University Press, 2021)
"Investigates the rhetorical strategies used by the Essenes in the Dead Sea Scrolls. Illustrates strategies based on identification, dissociation, entitlement, and interpretation in response to evolving historical contexts"--